THE SIMILARITIES AND DIFFERENCE BETWEEN EUROPEAN AND ASIAN TRANSPORT - Alijonov Komiljon Ikrom'son (TADQIQOTLAR.UZ, 2024)
Abstract: In this article, there is talk about the similarities and differences between European and Asian transportation systems and vehicles, and also, it provides information about the similarities and differences between transportation in eastern and western countries, and also provides information on how transportation is important in people's lives.